Groundwater management in a thermal area - a Portuguese case study - Ferreira, Nuno (2021)
Thermal mineral waters are a potential resource to the economic development of a region. In the north of Portugal, there are low enthalpy hot springs (T<150ºC), associated to major regional geological structures. The thermal area of Eirogo is an hydromineral occurrence located in the northern of Portugal (Braga region). The thermal area was exploited for a while, some years ago, and a sustainable exploitation is of great interest for the region. The thermal area is in the Ribeira de Pontes watershed of 45 km2 area, which recharge is estimated of about 125 mm/year. The area belongs to the Central Iberian Zone domain, dominated by granitic rocks that intruded metasedimentary rocks. There are quaternary deposits and a regolith layer of a few meter thickness, through which the infiltrated water circulates and discharges to streams. The thermal water is weakly mineralized (total mineralization = 425 mg/L) with an electrical conductivity of 660 µs/cm, pH of 8.3 and temperature approximately 24.5ºC, with a dominant sulphate-sodium type. The water sulphur enrichment confers properties for therapy applications. Isotopic data from the studied area indicate values for δ18O and δ2H of -4.79‰ and -27.7‰, respectively, suggesting a meteoric water contribution with deep-water mixing processes. In the thermal area, the drainage system is mainly controlled by geological structures, with a groundwater flows at high depth. The preferential recharge area of the thermal water is in the NE of the watershed, at an altitude of about 300 m. Groundwater flows through a large fault, orientated NE-SW, that crosses the watershed close to the thermal area. The water reaches a depth around 1300 m and, afterwards, comes back to surface through a highly fractured area, where occurs the thermal springs. The groundwater flow including recharge/discharge watershed areas is crucial for the management of hydromineral and thermal water resources.